Application of Nanobiotechnology in Medical Practice - Dhar, Srikanta; Sahoo, Rashmi Ranjan (International Journal of Psychosocial Rehabilitation, 2019)
Nanomedicine is the application to medicine of the nanobiotechnologies. The paper begins with the fundamentals of nanobiotechnology, followed by its uses in molecular diagnostics, nanodiagnostics, and advancements in drug discovery, design and distribution, like nanopharmaceutics. Biological treatments including vaccines, cell therapy, and gene therapy will be improved. Nanobiotechnology provides the basis for the creation of many modern medical and surgical technologies, such as nanorobots. It has applications in nearly every scientific field, where examples of neurological disorders (nanoneurology), cancer (nanooncology), cardiovascular disorders (nanocardiology), joint and bone diseases (nanoorthopedics), and infectious diseases are identified. Safety issues are also discussed about the in vivo use of nanomaterials. Nanobiotechnology will promote the integration of the diagnostics with therapy and facilitate the development of the personalized medicine, i.e. prescribing specific therapies that are best suited to an individual. Many of the changes have already begun and a significant effect in the practice of medicine will be experienced within a decade.